2021
DOI: 10.1007/s10803-021-05094-6
|View full text |Cite
|
Sign up to set email alerts
|

Are Autistic and Alexithymic Traits Distinct? A Factor-Analytic and Network Approach

Abstract: Despite the heterogeneity in autism, socioemotional difficulties are often framed as universal. Increasing evidence, however, suggests that socioemotional difficulties may be explained by alexithymia, a distinct yet frequently co-occurring condition. If, as some propose, autistic traits are responsible for socioemotional impairments, then alexithymia may itself be a symptom of autism. We aimed to determine whether alexithymia should be considered a product of autism or regarded as a separate condition. Using f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 65 publications
1
12
0
1
Order By: Relevance
“…Cronbach's α showed good internal consistencies for DIF ( α = .85) and DDF ( α = .74) and acceptable internal consistency for EOT ( α = .60). Most importantly in this research context is a recent study showing that despite their frequently observed covariation, autism and alexithymia traits measured with AQ and TAS can be considered as distinct constructs [44].…”
Section: Neuropsychological Assessmentmentioning
confidence: 98%
“…Cronbach's α showed good internal consistencies for DIF ( α = .85) and DDF ( α = .74) and acceptable internal consistency for EOT ( α = .60). Most importantly in this research context is a recent study showing that despite their frequently observed covariation, autism and alexithymia traits measured with AQ and TAS can be considered as distinct constructs [44].…”
Section: Neuropsychological Assessmentmentioning
confidence: 98%
“…One of these is alexithymia, which refers to difficulty in recognizing and describing one's and others' emotional states, [148][149][150] and which has been suggested as a possible explanation for the observed difficulties in social interactions and emotional reciprocity in individuals with ASD. [151][152][153][154] Another proposed mechanism is deficits in empathy, which is the ability to experience others' feelings and show concern for their suffering. [155][156][157][158] This has been suggested as a possible explanation for the central impairments in social interactions in ASD, including difficulties with emotional engagement.…”
Section: Computational Approaches and Clinical Populations Reveal Beh...mentioning
confidence: 99%
“…To explore the underlying psychological mechanisms of social-affective difficulties in individuals with ASD, several theories have been put forward. One of these is alexithymia, which refers to difficulty in recognizing and describing one's and others' emotional states [143][144][145], and has been suggested as a possible explanation for the observed difficulties in social interactions and emotional reciprocity in individuals with ASD [146][147][148][149]. Another proposed mechanism is deficits in empathy, which is the ability to experience others' feelings and show concern for their suffering [150][151][152][153].…”
Section: Atypical Social Trait Judgment In Asd Is Associated With Per...mentioning
confidence: 99%